2010
DOI: 10.1017/s0033291710001571
|View full text |Cite
|
Sign up to set email alerts
|

Face emotion recognition is related to individual differences in psychosis-proneness

Abstract: Background. Deficits in face emotion recognition (FER) in schizophrenia are well documented, and have been proposed as a potential intermediate phenotype for schizophrenia liability. However, research on the relationship between psychosis vulnerability and FER has mixed findings and methodological limitations. Moreover, no study has yet characterized the relationship between FER ability and level of psychosis-proneness. If FER ability varies continuously with psychosis-proneness, this suggests a relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 68 publications
1
64
4
Order By: Relevance
“…Concerning our use of a Web-based sample, data collected from Webbased samples have been found to be trustworthy estimates of true abilities, given appropriate subject filtering methods as were used in the present study (26)(27)(28). Data collected from www.testmybrain.org, in particular, have been found to be highly reliable (30); to yield laboratory-replicated developmental, aging, and individual differences effects (29,30,38,39); and to be comparable to data gathered in traditional laboratory-based samples on performance-related metrics (30,39).…”
Section: Methodsmentioning
confidence: 76%
“…Concerning our use of a Web-based sample, data collected from Webbased samples have been found to be trustworthy estimates of true abilities, given appropriate subject filtering methods as were used in the present study (26)(27)(28). Data collected from www.testmybrain.org, in particular, have been found to be highly reliable (30); to yield laboratory-replicated developmental, aging, and individual differences effects (29,30,38,39); and to be comparable to data gathered in traditional laboratory-based samples on performance-related metrics (30,39).…”
Section: Methodsmentioning
confidence: 76%
“…Previous research has shown evidence of an age-related decline in face recognition [35,36], which may be associated with age-related memory declines. While the Face recognition test of unfamiliar faces examines novel face processing, this task measures the ability to recognize known (famous) faces.…”
Section: Research Method: Materials and Proceduresmentioning
confidence: 99%
“…This type of qualitative equivalence (Buchanan, 2007) has been demonstrated for a range of cognitive and perceptual tests, including tests involving very brief, tachistoscopic presentation times (McGraw et al, 2000), measurement of subtle variations in response times (McGraw et al, 2000;Nosek, Banaji & Greenwald, 2002), accurate perception of simple visual stimuli (Krantz et al, 1997;Krantz & Dalal, 2000;McGraw et al, 2000;Senior, Phillips, Barnes & David, 1999), and focused attention (Birnbaum, 2000;Krantz & Dalal, 2000;McGraw et al, 2000). Moreover, a growing number of large-scale Web-based studies of cognition and perception have now been published that have demonstrated reliable, replicable, and theoretically consistent findings (Germine, Duchaine, & Nakayama, 2011;Germine & Hooker, 2011;Nosek et al, 2002;Soto, John, Gosling & Potter, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Web-based testing allows researchers to locate and study individuals with rare characteristics (e.g., Duchaine, Germine & Nakayama, 2007;Germine, Cashdollar, Düzel, & Duchaine, 2011). Indeed, the last several years have seen a rise in Webbased experiments across fields that rely on specific sample characteristics, including psychopathology (Germine & Hooker, 2011;Kendler, Myers, Potter & Opalesky, 2009), genetic epidemiology (Kendler et al, 2009), and behavioral genetics (Haworth et al, 2007;Wilmer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%